2022
DOI: 10.29303/jppipa.v8i6.2438
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Understanding Science Concepts for Prospective Elementary School Teacher Candidates

Abstract: Understanding the concept is one of the most important parts of realizing a teacher's professional competence. As elementary school teacher candidates, Elementary School Teacher Education students must have good conceptual understanding skills to realize the expected professional competence. This study aims to analyze elementary school teacher candidates' level of understanding of science concepts, specifically on temperature and heat, electricity, magnetic fields, and the solar system. This type of research i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…This indicates that early childhood preservice teachers are competent to carry out their role as professional teachers in the future. Concepts comprehension is a very important skill that must be owned by teachers and pre-service teachers when studying science (Hasnawati et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…This indicates that early childhood preservice teachers are competent to carry out their role as professional teachers in the future. Concepts comprehension is a very important skill that must be owned by teachers and pre-service teachers when studying science (Hasnawati et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…According to Devy et al (2022) who stated that the level of understanding of the science concept of the research sample was still relatively low, which was marked by repetition of complete answers, irrelevant and unclear answers. The results of subsequent studies showed that the level of understanding of science concepts by elementary school teachers was still below 50%, especially in the material of the sun, temperature and heat, electricity, magnetic fields, and the solar system (Hasnawati et al, 2022). Other studies have found that the level of students' conceptual understanding of lithospheric material is low, with an average of still below 50% of the 6 questions given (Laelandi et al, 2022).…”
Section: Introductionmentioning
confidence: 96%
“…Based on the previous research above, it means that during the learning process, students are not always optimal in absorbing information, especially in science subjects which contain many scientific concepts (Adiansyah Syahrul et al, 2015) and contains abstract concepts (Hasnawati et al, 2022). One of the reasons students are not optimal in absorbing information in learning is because of misconceptions (Hunaidah et al, 2022).…”
Section: Introductionmentioning
confidence: 99%